Self-Regulated Learning During the Covid-19 Pandemic - Herlina Herlina (JME (Journal of Mathematics Education), 2021)
Along with the change in learning modes during the pandemic, which was originally face-to-face directly to online learning, where teacher control is decreasing, Self Regulated Learning is a very important variable for students to have so that students can still learn even without teacher supervision. The purpose of this study was to describe the Self-Regulated Learning of 20 students who took the Learning and Learning course in the even semester of 2020/2021 FY. The method used in this research is that after participating in online learning through WhatsApp, Google Classroom, and Google Meet, at the end of the semester students are given a Self-Regulated Learning questionnaire through Google Forms and interviews. The research data were analyzed by descriptive statistical analysis. The results of the study found that the score of Self Regulated Learning was 88.28% from what was expected, there were 85% of students in the very good category, and 15% in the sufficient category. The highest indicator is self-control at 91.25%. While the indicator score of the lowest Self-Regulated Learning is self-confidence of 83.75%. The conclusion of this research is that students' Self Regulated Learning is already in the very good category but has not yet reached the highest score and there are still students in the fairly good category, so that it can still be increased to close to the expected 100%.